2003
DOI: 10.1103/physrevb.68.155310
|View full text |Cite
|
Sign up to set email alerts
|

Perturbative approach to the nonequilibrium Kondo effect in a quantum dot

Abstract: The theory of quantum transport through a dot under a finite bias voltage is developed using perturbation theory in the Keldysh formalism. It is found that the Kondo resonance splits into double peaks when the voltage exceeds the Kondo temperature, eV > kBTK , which leads to the appearance of a second peak in conductance, in addition to the zero-bias peak. The possible relevance of the new peak to the 0.7 conductance anomaly observed in quantum point contact is discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
134
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(150 citation statements)
references
References 25 publications
14
134
2
Order By: Relevance
“…It has been suggested that terms of order U 3 and U 4 might cause the peak to split. [63,64] However, a recent study with an improvement of the higher order corrections, which reproduces correctly the equilibrium expressions, indicates that the spectral density retains the qualitative features of the secondorder result. [66] Physically, one might expect that if the dot is hybridized with left and right leads at chemical potentials µ L and µ R with matrix elements V L and V R respectively, the effective distribution function fluctuates between that corresponding to µ L and µ R (at least if…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that terms of order U 3 and U 4 might cause the peak to split. [63,64] However, a recent study with an improvement of the higher order corrections, which reproduces correctly the equilibrium expressions, indicates that the spectral density retains the qualitative features of the secondorder result. [66] Physically, one might expect that if the dot is hybridized with left and right leads at chemical potentials µ L and µ R with matrix elements V L and V R respectively, the effective distribution function fluctuates between that corresponding to µ L and µ R (at least if…”
Section: Introductionmentioning
confidence: 99%
“…Recent use of perturbation theory in U/(π∆) for V ds = 0 was limited to the symmetric case, for calculations of the current noise, [62] and other properties including terms of third and fourth order in U, [63][64][65][66] and in particular in presence of magnetic field B, [64,65] motivated by recent experiments. [14][15][16] However, even in the symmetric case, the spin current is not conserved by the approximation when V ds = 0.…”
Section: Introductionmentioning
confidence: 99%
“…(12)(13)(14) define a set of coupled integral equations in the energy levels of the leads, ǫ k , whose solution yields the Green functions to be introduced in eq. (4). In these equations we have neglected expectation values of operators such as <χ † σχ −σĉ † k−σĉ kσ >, which…”
Section: Theorymentioning
confidence: 99%
“…After taking iϕ m → Φ and then iω n → ω + iη, this expression maps to the correct retarded self-energy in the Keldysh formalism [20].…”
mentioning
confidence: 99%